Cell Based Treatment of Autoimmune Diseases in Children - Jones, Olcay Y.; McCurdy, Deborah (Frontiers in Pediatrics, 2022)
Mesenchymal stem cells have recently been recoined as medicinal signaling cells (MSC) for their ability to promote tissue homeostasis through immune modulation, angiogenesis and tropism. During the last 20 years, there has been a plethora of publications using MSC in adults and to lesser extent neonates on a variety of illnesses. In parts of the world, autologous and allogeneic MSCs have been purified and used to treat a range of autoimmune conditions, including graft versus host disease, Crohn's disease, multiple sclerosis, refractory systemic lupus erythematosus and systemic sclerosis. Generally, these reports are not part of stringent clinical trials but are of note for good outcomes with minimal side effects. This review is to summarize the current state of the art in MSC therapy, with a brief discussion of cell preparation and safety, insights into mechanisms of action, and a review of published reports of MSC treatment of autoimmune diseases, towards the potential application of MSC in treatment of children with severe autoimmune diseases using multicenter clinical trials and treatment algorithms.